A comparative DFT study to investigate structural, electronic, and optical properties and bandgap engineering of 2D XSn4O7(X=Ba, Ca) and XSi4O9(X=Ba, Ca) materials for photocatalytic and solar cell applications - Jameel, Muhammad Hasnain; Tuama, Alaa Nihad; Mezan, Salim Oudah; A. Abdulkhudher, Basheer; Yasin, Aqeela; Mayzan, Mohd Zul Hilmi; Roslan, Muhammad Sufi; Mahdi Badi, Karrar; H. Alzubaidi, Laith (elsevier, 2025)
This comparison study is based on Density Functional Theory (DFT) to investigate the structural, electrical, and optical properties of two-dimensional XSn4O7(X=Ba, Ca) and XSi4O9(X = Ba, Ca) materials. First-principles analysis using the PBE-GGA (Perdew Burke-Ernzerhof Generalized Gradient Approximation) shows that Ca and Ba have a major impact on the electrical characteristics, energy band gap (Eg), and structural stability. The volume of crystal cells of XSn4O7 (X=Ba, Ca) and XSi4O9(X= Ba, Ca) decreased from 581.794 to 354.022A3 due to the ionic radii difference of Ba and Ca from 268 to 231 pm respectively. The calculated energy bandgaps (Eg) are 4.28, 2.14, 0.88, and 0.34 eV for BaSi4O9, CaSi4O9, BaSn4O7, and CaSn4O7 respectively. These energy bandgap values indicate that BaSi4O9 and CaSi4O9 have wide band gaps while BaSn4O7 and CaSn4O7 exhibit small energy band gaps, making them suitable and more responsive to UV visible light. The detailed results of optical conductivity show that the peaks of optical conductance for 2D XSn4O7(X=Ba, Ca) and XSi4O9(X=Ba, Ca) reach maximum values of 1.7, 2.2, 2.9, and 6 cm− 1 in the ultraviolet spectrum at energies ranging from 0 to 40eV, respectively. Two dimensional XSn4O7 (X=Ba, Ca) and XSi4O9 (X=Ba, Ca) materials showed maximal optical absorption with absorption coefficient α(w) values of 4.1 × 105 , 2.2 × 105 , 1.5 × 105 , and 1 × 105 cm-1, respectively. In comparison to other materials, the highest absorption is found in BaSn4O7 and CaSn4O7, with absorption coefficients of 4.1 × 105 cm-1 and 2.2 × 105 cm-1, respectively. Our findings indicate that 2D XSn4O7(X=Ba, Ca) and XSi4O9(X=Ba, Ca) oxides, are appropriate for photocatalytic and solar cell applications.